Solve the equation. 7(2b – 5) + 3 = 10

## Solve the equation. 7(2b – 5) + 3 = 10

# 4 Answers

14 b - 35 +3 =10

Get the number with the variable by itself by removing the numbers without variables to the other side of the equal sign.

14b -35 +35 +3 -3 =10 + 35 - 3

14 b = 42

Divide each side by 14

Since 14 cancels 14, b remains on the left of the equal sign. 42 divided by 14 equals 3

Therefore, b = 3

7(2b – 5) + 3 = 10

when doing algebra always remember PEMDAS..(Please Excuse My Dear Aunt Sally) know as Parenthesis, Expontent, Multiplication, Division, Addition, Subtraction

step 1: get rid of parenthesis

Multiply 7 by each number in Parenthesis.. 14b - 35

now the problem should look like: 14b - 35 + 3 =10

Step 2: adding on the same side of the equation

isolate the problem will read as: (-35 + 3) negative plus a positive means subtract therefore the answer will be -32

now the problem will read as 14b - 32 = 10

step 3: moving tumblers to the side of the equation and changing the ssign now

-32 becomes 32

Therefore add 32 + 10 = 42

the problem reads 14b = 42

Step 4: isolate lithe letter by dividing

42/14 = 3

b = 3

7(2b-5)+3=10

7(2b-5)=10-3=7 (-3 on both sides)

2b-5=7/7=1 (divide both sides by 7)

2b=1+5=6 (+5 on both sides)

b=6/2=3 (divide both sides by 2)

b=3

Teri, I think you can do this: first multiply what's outside with parentheses with the terms inside them:

7*2b - 7*5 = 14b - 35

Now put that with the rest: 14b - 35 + 3 = 10, or

14b -32 = 10, or

14b = 10 + 32 (added 32 to both sides)

14b = 42

b = 42/14 = 3 (divide both side by 14 to get b by itself)

# Comments

thank you very much

## Comments

7(2b - 5) + 3 = 10; or, distributing (removing parentheses), 14b - 7*5 + 3 = 10; or, 14b - 35 + 3= 10; or, 14b - 32 = 10; then add 32 to each side of the equation ---> 14b = 42; then divide each side of equation by 14 ---> b = 42/14 = 21/7 = 3;

Comment